2019
DOI: 10.1002/jmv.25482
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐34a aggravates coxsackievirus B3‐induced apoptosis of cardiomyocytes through the SIRT1‐p53 pathway

Abstract: Viral myocarditis is inflammation of the myocardium mainly caused by a viral infection, and coxsackievirus B3 (CVB3) infection is one of the most common. It is well known that cardiomyocyte apoptosis is involved in the pathogenesis of viral myocarditis. microRNAs (miRNAs, miRs) are endogenous noncoding oligoribonucleotides involved in various pathological conditions, and miR-34a is one of the miRNAs causing apoptosis. Whether miR-34a participates in cardiomyocyte apoptosis during CVB3 infection and the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…miRNAs are a class of small, single-stranded noncoding RNAs widely found in eukaryotes that block the translation of their target mRNAs via posttranscriptional regulation, ultimately inhibiting target gene expression (Tang et al, 2016). In addition to engaging in the abovementioned mechanisms, CVB3 can target miRNA-34a in host cells to downregulate the histone deacetylase SIRT1, consequently increasing Bax expression, inhibiting Bcl-2 expression and inducing apoptosis (Jiang et al, 2019). Furthermore, p53dependent apoptosis can be promoted by upregulation of the expression of the histone deacetylase HDAC1 via miRNA-34a (Zhou et al, 2015).…”
Section: Other Mechanisms Of Apoptosis Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are a class of small, single-stranded noncoding RNAs widely found in eukaryotes that block the translation of their target mRNAs via posttranscriptional regulation, ultimately inhibiting target gene expression (Tang et al, 2016). In addition to engaging in the abovementioned mechanisms, CVB3 can target miRNA-34a in host cells to downregulate the histone deacetylase SIRT1, consequently increasing Bax expression, inhibiting Bcl-2 expression and inducing apoptosis (Jiang et al, 2019). Furthermore, p53dependent apoptosis can be promoted by upregulation of the expression of the histone deacetylase HDAC1 via miRNA-34a (Zhou et al, 2015).…”
Section: Other Mechanisms Of Apoptosis Inductionmentioning
confidence: 99%
“…Enteroviruses regulate miRNAs to induce apoptosis. Apoptosis induced by enterovirus infection is associated with the regulation of microRNAs (miRNAs)(Chang et al, 2015;Jiang et al, 2019). The red dotted line indicates the site of enteroviral action, and the red solid arrows indicate the up-or downregulation of the expression of each protein.…”
mentioning
confidence: 99%
“…Numerous studies have indicated the pivotal roles of miRNAs in the initiation and development of various human diseases, including malignancies (22), metabolic diseases (23) and cardiovascular diseases (24). In sepsis, there are also functional miRNAs that are linked to the progression of the disease by the regulation of inflammatory response, such as miR-150 (25) and miR-27a (26), e.g.…”
Section: Discussionmentioning
confidence: 99%
“…miR-19b contributed to cardiac arrhythmia through repression of gap junction protein α1 (GJA1) in a mouse model of VMC (154). miR-34a promoted cardiomyocyte apoptosis by downregulating sirtuin 1 (SIRT1), an inhibitory factor to p53-dependent apoptosis (155). miR-141-3p alleviated the inflammatory response by inhibiting signal transducer and activator of transcription 4 (STAT4) in mice with EAM (156).…”
Section: Miscellaneous Mirnasmentioning
confidence: 99%